2022
DOI: 10.1186/s13014-021-01963-7
|View full text |Cite
|
Sign up to set email alerts
|

Gastric side effects and the stomach dosimetric analysis in left-sided breast cancer radiotherapy in free-breathing and deep inspiration breath-hold technique

Abstract: Background Adjuvant radiotherapy following surgery reduces the local recurrence and improves the prognosis. However, a considerable part of patients developed digestive reaction in daily treatment. In order to explore the correlation between breast radiotherapy and gastric toxicity, we investigated the clinic symptoms and stomach dose during DIBH or FB mode while left-sided breast cancer patients (LSBCP) receiving radiotherapy. Methods In the study… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Also, in accordance with the present studyPruijssen, et al, (2022) reported that in patients receiving head and neck radiotherapy fatigue was highly prevalent: 51.7% experienced severe fatigue (subjective fatigue score ≥ 35). On the same way, the study ofYang, et al, (2022) reported that, of all the patients receiving radiotherapy, 12.1% (15/124) patients developed gastric symptoms including loss of appetite and nausea.In the same way, Iglseder, et al, (2022) reported that, 20% of the patients receiving radiotherapy experienced acute Neurological side effects as headache due to increased intracranial pressure. This finding in agreement with the results of the study done bySourati, et al, (2017) about Acute side effects of radiation therapy in cancer patients revealed that the most frequently reported side effects were fatigue, headache, anorexia or nausea, and vomiting.…”
mentioning
confidence: 79%
“…Also, in accordance with the present studyPruijssen, et al, (2022) reported that in patients receiving head and neck radiotherapy fatigue was highly prevalent: 51.7% experienced severe fatigue (subjective fatigue score ≥ 35). On the same way, the study ofYang, et al, (2022) reported that, of all the patients receiving radiotherapy, 12.1% (15/124) patients developed gastric symptoms including loss of appetite and nausea.In the same way, Iglseder, et al, (2022) reported that, 20% of the patients receiving radiotherapy experienced acute Neurological side effects as headache due to increased intracranial pressure. This finding in agreement with the results of the study done bySourati, et al, (2017) about Acute side effects of radiation therapy in cancer patients revealed that the most frequently reported side effects were fatigue, headache, anorexia or nausea, and vomiting.…”
mentioning
confidence: 79%
“…Colossal amounts of studies have shown that amid left breast cancer radiotherapy, DIBH technology can separate the heart from mammary gland position, so as to signi cantly shrink the high dose volume and mean dose of the heart, and reduce heart disease risks associated [18][19][20] . Meanwhile, coupled with DIBH technology, it can also increase the lung volume, reduce the lung tissue density, which lowers the irradiation dose in the lung 13 , and slump the irradiation dose of the contralateral breast, stomach and liver to varying degrees 21,22 . Although DIBH technique is widely used in left-sided breast cancer, there are few reports on the clinical application of DIBH technique in right-sided breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In the equation, p i represented the sampling value obtained by compressed sensing with the number of n. R was the observation base composed of a set of observation vectors (ϕ i ) n i�1 . e key to construct a signal was to find the sparse representation of the signal in a certain variation domain ∀, which could be solved by means of the L0 norm optimization in (2). min ‖∀ε‖ 0 zt, p � ϕ ε.…”
Section: Improved Art Under L0 Algorithmic Approachmentioning
confidence: 99%
“…e ability to resist infection and tumor defense in patients with acquired immune de ciency syndrome (AIDS) decreased due to immunode ciency. It is very easy to complicate with various tumors, and the probability of su ering from tumors is about 50 times of the normal population [1][2][3].…”
Section: Introductionmentioning
confidence: 99%